Can platelet BACE1 levels be used as a biomarker for Alzheimer's disease? Proof-of-concept study. (May 2013) - Decourt, Boris; Walker, Aaron; Gonzales, Amanda; Malek-Ahmadi, Michael; Liesback, Carolyn; Davis, Kathryn J.; Belden, Christine M.; Jacobson, Sandra A.; Sabbagh, Marwan N.
<x xml:space="preserve">Abstract</x> To date there is no validated peripheral biomarker to assist with the clinical diagnosis of Alzheimer's disease (AD). Platelet proteins have been studied as AD biomarkers with relative success. In this study, we investigated whether platelet BACE1 levels differ between AD and cognitively normal (CN) control patients. Using a newly developed ELISA method, we found that BACE1 levels were significantly lower in AD compared to CN subjects. These data were supported by the observation that several BACE1 isoforms, identified by Western blotting, were also lower in AD platelets. This proof-of-concept study provides evidence for testing platelet BACE1 levels as a peripheral AD biomarker using a novel, sensitive and inexpensive method.